EGFR-mediated local invasiveness and response to Cetuximab in head and neck cancer - Zhou, Jiefu; He, Min; Zhao, Qiong; Shi, Enxian; Wang, Hairong; Ponkshe, Vaidehi; Song, Jiahang; Wu, Zhengquan; Ji, Dongmei; Kranz, Gisela; Tscherne, Anna; Schwenk-Zieger, Sabina; et al. (Molecular cancer, 2025)
BACKGROUND: Recurrent/metastatic head and neck squamous cell carcinoma (R/M-HNSCC) is a severe, frequently lethal condition. Oncogene addiction to epidermal growth factor receptor (EGFR) is a hallmark of HNSCC, but the clinical efficacy of EGFR-targeted therapies remains low. Understanding molecular networks governing EGFR-driven progression is paramount to the exploration of (co)-treatment targets and predictive markers. - METHODS: We performed function-based mapping of differentially expressed genes in EGFR-mediated local invasion (fDEGs) using photoconvertible tracers and RNA-sequencing (RNA-seq) in a cellular 3D-model. - RESULTS: Upon alignment with public single-cell RNA-seq (scRNA-seq) datasets and HNSCC-specific regulons, a gene regulatory network of local invasion (invGRN) was inferred from gene expression data, which was overrepresented in budding tumors. InvGRN comprises the central hubs inhibin subunit beta alpha (INHBA) and snail family transcriptional repressor 2 (SNAI2), and druggable fDEGs integrin subunit beta 4 (ITGB4), laminin 5 (LAMB3/LAMC2), and sphingosine kinase 1 (SPHK1). Blockade of INHBA repressed local invasion and was reverted by activin A, laminin 5, and sphingosine-1-phosphate, demonstrating a functional interconnectivity of the invGRN. Epithelial-to-mesenchymal transition (EMT) of malignant cells and the invGRN are induced by newly defined EGFR-activity subtypes with prognostic value that are promoted by amphiregulin (AREG) and epiregulin (EREG). Importantly, co-inhibition of SPHK1 showed synthetic effects on Cetuximab-mediated invasion blockade and high expression of selected fDEGs was associated with response to Cetuximab in patient-derived xenotransplantation (PDX) and R/M-HNSCC patients. - CONCLUSIONS: We describe an actionable network of EGFR-mediated local invasion and define druggable effectors with predictive potential regarding the response of R/M-HNSCC to Cetuximab.